Ukuran Perusahaan dan Media Exposure Terhadap Pengungkapan Corporate Social Responsibility dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Naufal Bayu Ardhana; Tantina Haryati (IPM2KPE, 2023)
This study aims to examine the effect of institutional ownership as a moderating variable on company size and media exposure on disclosure of corporate social responsibility (CSR) in companies in the mining sector. The research method used is quantitative through company financial data. Research results a) The size of the company on the disclosure of Corporate Social Responsibility (CSR) has a positive regression coefficient and the resulting p-value (sig.) is below 5% (sig. = 0.000) or 0 <0.05; b) media exposure to Corporate Social Responsibility (CSR) disclosure has a positive regression coefficient with a p-value (sig.) resulting in below 5% (sig = 0.000) or 0 <0.05; c) institutional ownership moderates the relationship between firm size and Corporate Social Responsibility (CSR) disclosure which has a negative sign with a p-value (sig.) which is below 5% (sig. = 0.043) and the coefficient value is -0.120; d) institutional ownership moderates media exposure and disclosure of Corporate Social Responsibility which has a p-value (sig.) which is above 5% (sig. = 0.083) and has a negative coefficient value of -0.162. In conclusion, company size and media exposure have a significant effect on the disclosure of Corporate Social Responsibility. Meanwhile, institutional ownership as a moderating variable negatively affects the relationship between firm size and Corporate Social Responsibility (CSR) disclosures and institutional ownership as a moderating variable negatively affects the relationship between media exposure and Corporate Social Responsibility (CSR) disclosures. Keywords: Corporate Social Responsibility, Institutional Ownership, Media